2020
DOI: 10.1177/1099636220909946
|View full text |Cite
|
Sign up to set email alerts
|

Co/aniline blue/silicon sandwich hybrid heterojunction for photodiode and low-temperature applications

Abstract: The temperature dependence of the current–voltage and room temperature capacitance–voltage measurements of Co/aniline blue/ n-Si sandwich-type rectifying device was investigated.Furthermore, the effects of the illumination on the current–voltage measurements were tested with 100 mW/cm2 light intensity, and it was seen that Co/aniline blue/ n-Si sandwich-type device showed a clear response to illumination, and it may be a candidate for solar cells or photodiode applications. The rectifying device parameters, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The ideality factor, saturation current and barrier height values were calculated and resistance rather than more than unity (Cifci et al, 2018;Kacus et al, 2020) These results can be indicated to good response time according to literature (Hu et al, 2021). These results can be indicated to good response time according to literature (Hu et al, 2021).…”
Section: Methodsmentioning
confidence: 74%
“…The ideality factor, saturation current and barrier height values were calculated and resistance rather than more than unity (Cifci et al, 2018;Kacus et al, 2020) These results can be indicated to good response time according to literature (Hu et al, 2021). These results can be indicated to good response time according to literature (Hu et al, 2021).…”
Section: Methodsmentioning
confidence: 74%
“…This case may be described by the lateral inhomogeneity of BHs. [23][24][25][26][27][28][29][30] According to GD model, the formed of BH between semiconductor and Schottky contact hasn't homogenous and a mean-BH ECS Journal of Solid State Science and Technology, 2023 12 083010 ( B0 Φ ¯) is defined in Eq. 9a, depending on the standard-deviation S (σ ) of BH.…”
Section: Resultsmentioning
confidence: 99%
“…The high ideality factor values at the Al/CoPOM/p‐Si and Al/NiPOM/p‐Si devices can be attributed to barrier inhomogeneity and interfacial POM layers as well as series resistance rather than more than unity. [ 50,51 ]…”
Section: Resultsmentioning
confidence: 99%
“…The The high ideality factor values at the Al/CoPOM/p-Si and Al/ NiPOM/p-Si devices can be attributed to barrier inhomogeneity and interfacial POM layers as well as series resistance rather than more than unity. [50,51] The threshold voltages of the Al/CoPOM/p-Si and Al/ NiPOM/p-Si devices were determined as 0.38 and 0.25 V under dark, respectively. The threshold voltage changes with changing light power have been shown in Figure S4a (Supporting Information).…”
Section: Electrical Characteristics Of the Al/copom/p-si And Al/nipom...mentioning
confidence: 99%